Effect of tio2 in fine zircon sintering and properties - Gauna, Matias Roberto (2021)
The effect of the TiO2 addition in the ceramic processing of dense zircon materials from zircon fine powders was established. The addition of TiO2 (5-10 wt %) permitted to obtain dense ceramics at lower temperatures (100-150o C below), with comparable mechanical behavior. The thermochemical processes were described after a multi-technique experimental approach, which included a sintering analysis, powder X-Ray diffraction analysis (XRD), scanning electronic microscopy (SEM) and Vickers hardness of the polished dense obtained ceramics. After 1400o C heating programs, the added TiO2 acts as a sintering aid with no important chemical reactions, and presented improved mechanical behavior in comparison with pure zircon ceramics. On the other side, in samples fired at 1500o C, TiO2 partially (≈50 %) reacts with zircon, forming ZrTiO4, while the formed SiO2 goes to the grain boundaries. Samples with 5 wt % TiO2 present better mechanical behavior than the ones with 10 wt%. The performed mechanical characterization indicates the merits of the material processed by this inexpensive processing route. Developed density, hardness (≈10 GPa) and fracture toughness (≈2 MPa.m-1/2) are comparable with the best figures reported.